Implementation of Career Guidance System in Undergraduate Study for Smooth Transition to Future Prospects - Rathod, S. S.; Gharpure, Prachi (Journal of Engineering Education Transformations, 2016)
In 2013, authors hypothesized that students would improve if motivated and mentored appropriately to pursue career in the chosen path. The primary goal is to facilitate students' successful transfer in the chosen path by maintaining healthy relevant learning environment. This study evaluates whether the implemented career guidance program in the electronics engineering department increases self-esteem, confidence and skill to pursue career in the chosen path by the student. Results indicate that students show higher levels of academic performance and achievements. In this paper, authors also propose curriculum scheme with choice based career guidance.